PENGARUH PROFITABILITAS, EARNING PER SHARE (EPS) DAN DIVIDEND PAYOUT RATIO (DPR) TERHADAP HARGA SAHAM - Fauza, Mochamad Sayiddani; Mustanda, I Ketut (E-Jurnal Manajemen; Vol 5 No 12 (2016), 2017)
The purpose of this study was to determine the effect of profitability, earnings per share and dividend payout ratio on stock prices. The research design used in this study are associative, which is to investigate the influence of the independent variable profitability, EPS and Parliament on the dependent variable stock price. The type of data in this study is the quantitative data obtained through secondary sources. Object of this research is the share price of listed companies in the stock index LQ 45. The population in this study are 30 companies listed in the stock index LQ 45 which is continuously paid a dividend every year during the period 2013-2014. Number samples are 28 companies that are determined by random sampling technique. The analysis technique used is the technique of panel data regression analysis with the help of eviews application. Based on the analysis we concluded that profitability, Earning Per Share and Dividend Payout Ratio is partially significant positive effect on stock prices.
Keywords: Profitability, Earning Per Share, Dividend Payout Ratio, Stock Price, LQ 45